Field-ion microscopic observation of a twin boundary in iridium - Ranganathan S.; Chandrasekharaiah M.N. (My University, 2025)
Twin boundaries in field-ion micrographs are expected to show matching of rings of prominent planes in the matrix crystal with rings of other prominent planes in the twin crystal. This paper offers additional experimental verification of this contrast feature and shows the usefulness of this concept in identifying orientation relationships in bicrystals without the uncertainty involved in the assumption on that the field-ion projection corresponds to any of the standard projections. © 1976.